Albuminuria: An Underappreciated Risk Factor for Cardiovascular Disease - Joshua I Barzilay; Youssef M. K. Farag; Jeffrey Durthaler (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
ABSTRACT: Albuminuria, an established biomarker of the progression of chronic kidney disease, is also recognized as a biomarker for the risk of cardiovascular disease. Elevated urinary albumin excretion indicates kidney damage and systemic vascular disease, including myocardial capillary disease and arterial stiffness. Albuminuria is associated with an increased risk of coronary artery disease, stroke, heart failure, arrhythmias, and microvascular disease. There are now several therapeutic agents that can lead to albuminuria lowering and a reduction in cardiovascular risk. However, screening for albuminuria is still low. Considering the importance of multidisciplinary management of patients with cardiovascular disease, it is crucial that health care professionals managing such patients are aware of the benefits of albuminuria surveillance and management.